Compositional changes in soil water and runoff water following managed burning on a UK upland blanket bog - Clay, G.D.; Worrall, F.; Fraser, E.D.G. (Journal of Hydrology, 2010)
This study examines the effect managed rotational burning has on soil water and runoff water compositions at the end of a 10 year burning cycle and into the year following a managed burn. This study includes aluminium, iron, calcium, sodium, magnesium, potassium, sulphate, chloride, bromide, fluoride, phosphate and nitrate along with pH, conductivity and DOC. The main findings of this study are: 1. The presence of burning leads to lower concentrations of species associated with deep water sources in both soil and runoff waters. 2. Following burning, soil water has increased concentrations in shallow soil water components (i.e. Al, Fe). Conversely runoff water shows a decrease in the concentration of shallow water components 3. Principal component analysis shows that in the post-burn period, soil water is less mixed with rainwater and runoff water becomes more rainwater-like in composition, i.e. compositions of soil and runoff have diverged as a result of the burn.
EPrint Processing Status: Author unable to supply full text
Keywords: Burning; Grazing; Flowpaths; Soil water; Runoff; Peat.